2014
DOI: 10.1155/2014/379890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blueberry Juice in Mouse Azoxymethane‐Induced Aberrant Crypts and Oxidative Damage

Abstract: Blueberry is a plant with a number of nutritional and biomedical capabilities. In the present study we initially evaluated the capacity of its juice (BJ) to inhibit the number of aberrant crypts (AC) induced with azoxymethane (AOM) in mouse. BJ was administered daily by the oral route to three groups of animals during four weeks (1.6, 4.1, and 15.0 μL/g), respectively, while AOM (10 mg/kg) was intraperitoneally injected to the mentioned groups, twice a week, in weeks two and three of the assay. We also include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…After washing with PBS pH 7.4 (4 °C), colon tissue was placed in a Petri dish, embedded with solid paraffin, and fixed with 4% formaldehyde in PBS (pH 7.4) for 24 h. Afterward, each tissue was stained with 4% methylene blue in PBS for 2 min. Subsequently, the number of crypts was identified and imaged with an optical microscope (Carl Zeiss, Primo Star) at 10X magnification [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…After washing with PBS pH 7.4 (4 °C), colon tissue was placed in a Petri dish, embedded with solid paraffin, and fixed with 4% formaldehyde in PBS (pH 7.4) for 24 h. Afterward, each tissue was stained with 4% methylene blue in PBS for 2 min. Subsequently, the number of crypts was identified and imaged with an optical microscope (Carl Zeiss, Primo Star) at 10X magnification [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…Polyphenol-rich blueberry juice exerted a protective effect in AOM-induced ACF formation in mouse, and reduced the levels of oxidized DNA bases (8-hydroxy-2′-deoxyguanosine, 8-OHdG), and increased the antioxidant capacity to capture the 2,2-diphenil-1-picrilhydracil radical (DPPH) ex vivo [47].…”
Section: Polyphenols As Antioxidants and Their Role In Chemopreventionmentioning
confidence: 99%
“…Even though this effect is yet to be confirmed in vivo, the suggestion may be valid in light of the fact that a number of reports have showed concordance between the in vitro and in vivo results. Furthermore, previous studies have demonstrated that besides forming colon ACF in mouse, AOM also induced in vivo oxidation to lipids, proteins, and DNA, and that chemopreventive agents act, at least partially, by blocking such oxidative damage (41,42,43).…”
Section: Nutrition and Cancermentioning
confidence: 99%